American copper - Ray, Shann (Unbridled Books, 2015)
As Evelynne Lowry, the daughter of a copper baron, comes of age in early 20th century Montana, the lives of horses dovetail with the lives of people and her own quest for womanhood becomes inextricably intertwined with the future of two men who face nearly insurmountable losses<U+2014>a lonely bull rider named Zion from the Montana highline, and a Cheyenne team roper named William Black Kettle, the descendant of peace chiefs. An epic that runs from the Sand Creek Massacre of 1864 to the ore and industry of the 1930s, American Copper is a novel not only about America's hidden desire for regeneration through violence but about the ultimate cost of forgiveness and the demands of atonement. It also explores the genocidal colonization of the Cheyenne, the rise of big copper, and the unrelenting ascent of dominant culture. Evelynne's story is a poignant elegy to horses, cowboys both Native and Euro-American, the stubbornness of racism, and the entanglements of modern humanity during the first half of the twentieth century. Set against the wide plains and soaring mountainscapes of Montana, this is the American West re-envisioned, imbued with unconditional violence, but also sweet, sweet love.